PROSPEK DAN TANTANGAN BANK SYARIAH PASCA MERGER (BANK SYARIAH BNI, BRI DAN MANDIRI) - Supriyanto, Dodi; Aulia, Syafitri Nur (STIE Ekuitas, 2021)
One of the government's policies to strengthen domestic Islamic financial institutions is by implementing a merger of three Islamic commercial banks, which are state-owned subsidiaries, namely Bank Syariah Mandiri, BRI Syariah, and BNI Syariah, where BRI Syariah will be the surviving entity or entity that receives this merger. However, this policy could create new problems or challenges for merged banks, such as in the areas of human resources, capital, and market share. This study aims to determine the prospects and challenges of post-merger Islamic banking. The descriptive research approach was utilized. The documentation study data collecting approach was employed in this investigation. From 2013 to 2017, the data was derived from the quarterly financial reports of Bank BNI Syariah, PT. Bank BRI Syariah, Tbk, and Bank Mandiri Syariah. This study's findings include market share, Third-party Funds, Capital Adequacy Ratio (CAR), other ratios, and the number of employees.